A ANALYSIS IN SOLIDWORKS SOFTWARE OF THE STRENGTHS GENERATED IN THE UNDERGROUND PART OF THE WAGONS AS A RESULT OF THE IMPACT OF FORCE ON THE ENTIRE WHEELS OF WAGONS - Шокучкоров, Курбонназар; Рузметов, Ядгор (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The purpose In this article, the vertical and horizontal forces acting on the wheel of a freight car are calculated using formulas, and the calculated forces are determined by placing the wheel on a 3D model using Solidworks software. Methods. The 3D model of the wheel is drawn using the Solidworks program according to GOST 10791-2011, and the forces calculated through the simulation section are placed on the rolling surface, and the results are tabulated. Results. When the calculated forces were applied to the wheel through the simulation section of the SolidWorks program, the minimum stress on the bottom part of it was 10 MPa, and the maximum stress was 120 MPa. The stress results were calculated 60 times, that is, the forces were divided into 12 blocks and the wheel was turned five times. Efforts were made after each direction and results were obtained Summary. The conclusion of the scientific article is that the tension generated in the wheel is related to the thickness of the tread. When the wall thickness was 70 mm, when the operational maximum force was applied to it, a stress of 80 MPa was generated. During the service life, the value of voltages in the calculation field changes in each direction